Suppressive effect of compact bone-derived mesenchymal stem cells on chronic airway remodeling in murine model of asthma - FİLİNTE, DENİZ; ÖĞÜLÜR, İSMAİL; AKKOÇ, TUNÇ (ELSEVIER SCIENCE BV, 2014)
New therapeutic strategies are needed in the treatment of asthma besides vaccines and pharmacotherapies. For the development of novel therapies, the use of mesenchymal stem cells (MSCs) is a promising approach in regenerative medicine. Delivery of compact bone (CB) derived MSCs to the injured lungs is an alternative treatment strategy for chronic asthma. In this study, we aimed to isolate highly enriched population of MSCs from mouse CB with regenerative capacity, and to investigate the impact of these cells in airway remodeling and inflammation in experimental ovalbumin-induced mouse model of chronic asthma. mCB-MSCs were isolated, characterized, labeled with GFP and then transferred into mice with chronic asthma developed by ovalbumin (OVA) provocation. Histopathological changes including basement membrane, epithelium, subepithelial smooth thickness and goblet cell hyperplasia, and MSCs migration to lung tissues were evaluated. These histopathological alterations were increased in ovalbumin-treated mice compared to PBS group (P < 0.001). Intravenous administration of mCB-MSC significantly reduced these histopathological changes in both distal and proximal airways (P < 0.001). We showed that GFP-labeled MSCs were located in the lungs of OVA group 2 weeks after intravenous induction. mCB-MSCs also significantly promoted Treg response in ovalbumin-treated mice (OVA + MSC group) (P < 0.037). Our studies revealed that mCB-MSCs migrated to lung tissue and suppressed histopathological changes in murine model of asthma. The results reported here provided evidence that mCB-MSCs may be an alternative strategy for the treatment of remodeling and inflammation associated with chronic asthma. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Airway remodeling; BALB/c; Chronic model of asthma; Mesenchymal stem cells; Ovalbumin; REGULATORY T-CELLS; PROGENITOR CELLS; STROMAL CELLS; INFLAMMATION; DISEASE; CULTURE; LYMPHOCYTES; EXPANSION; MODULATE; MICE